2021
DOI: 10.3390/molecules26040845
|View full text |Cite
|
Sign up to set email alerts
|

Neurotoxic Effect of Flavonol Myricetin in the Presence of Excess Copper

Abstract: Oxidative stress (OS) induced by the disturbed homeostasis of metal ions is one of the pivotal factors contributing to neurodegeneration. The aim of the present study was to investigate the effects of flavonoid myricetin on copper-induced toxicity in neuroblastoma SH-SY5Y cells. As determined by the MTT method, trypan blue exclusion assay and measurement of ATP production, myricetin heightened the toxic effects of copper and exacerbated cell death. It also increased copper-induced generation of reactive oxygen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 80 publications
(133 reference statements)
0
11
0
Order By: Relevance
“…In Myrtle extract, the main polyphenolic components are Myricetin-3-O-rham (36.68%), Myricetin-3-O-gallac (33.20%), Miricetin (14.48%) and 5-O-galloyl quinic Acid (7.96%). Myricetin can act as an antioxidant and as pro-oxidant, possesses six hydroxyl groups and thus has great potential for participating in oxidation and redox cycling as described in [39]. Its potential to act as a pro-oxidant due to its tendency to undergo autoxidation depending upon its environment resulting in changes in SOD and CAT activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Myrtle extract, the main polyphenolic components are Myricetin-3-O-rham (36.68%), Myricetin-3-O-gallac (33.20%), Miricetin (14.48%) and 5-O-galloyl quinic Acid (7.96%). Myricetin can act as an antioxidant and as pro-oxidant, possesses six hydroxyl groups and thus has great potential for participating in oxidation and redox cycling as described in [39]. Its potential to act as a pro-oxidant due to its tendency to undergo autoxidation depending upon its environment resulting in changes in SOD and CAT activity.…”
Section: Discussionmentioning
confidence: 99%
“…Biomarkers for lipid peroxidation (MDA) in tissues were determined by measuring the content of TBARS using a method described by our previous paper [38,39]. Briefly, after centrifugation supernatant of the homogenized tissue (200 µL) was mixed with 200 µL of 8.1% sodium dodecyl sulphate (SDS), 1.5 mL of 20% acetic acid (pH = 3.5), and 1.5 mL of 0.81% thiobarbituric acid, and incubated at 95 • C for 60 min.…”
Section: Antioxidant Status Of Tissuesmentioning
confidence: 99%
“…However, the full potential of flavonoids in neuroprotection is far from closure. It is known that in the presence of transient metals such as copper and iron, flavonoids may act as pro-oxidants and contribute to increases in ROS, intensifying OS and threatening neuronal viability [123,196,197]. Moreover, flavonoids are metabolically altered in the gut after oral consumption.…”
Section: Flavonols As Therapeutic Option In Neurodegenerative Diseasesmentioning
confidence: 99%
“…Finally, it should be mentioned that, in certain circumstances, myricetin, similar to quercetin, may exert a neurotoxic effect when applied together with excess copper. In SH-SY5Y cells, myricetin promoted the production of ROS and caspase-independent cell death without affecting p53 expression and its target Bax [197]. Hence, the adverse effects of quercetin, myricetin and potentially some other flavonols should not be neglected.…”
Section: Myricetinmentioning
confidence: 99%
“…Alcohol addiction, like different substance addictions, causes alcohol-seeking (craving) and maintenance of alcohol use, involving multiple neurotransmitter systems such as dopamine, glutamate, γaminobutyric acid (GABA), serotonin, and peroxisome proliferator-activated receptors (PPARs) system [10]. The publications review indicates that myricetin was demonstrated to affect the glutaminergic system, GABAergic system, peroxisome proliferator-activated receptors (PPARs) [11][12][13][14][15][16]. For example, an earlier investigation demonstrated that NMDA receptor antagonists reduced the development of ethanol-CPP [17][18][19].…”
Section: Introductionmentioning
confidence: 99%